Da'wa in Social Media: The Views of Ustad Hanan Attaki and Felix Siauw to The Hijrah Phenomenon - Nafik Muthohirin (Fakultas Studi Islam dan Peradaban, Universitas Muhammadiyah Yogyakarta, 2021)
This article examines the views of Ustad Hanan Attaki (UHA) and Ustad Felix Siauw, who use social media as a medium of preaching. The utilization of the internet as a new way of preaching Islam has helped shape contemporary forms of religious thinking and behavior for Muslim youth in Indonesia. One of them is marked by the emergence of the trend of hijrah in their community. This study aimed to explain the Islamic views of UHA and Siauw, which have implications for the emergence and development of the hijrah trend. This research focuses on extracting data through observations on a number of predetermined social media accounts, field participation and interviews, and puts forward literature studies on the fragmentation of religious authority as a result of the emergence of a number of popular ustadz who use social media as a new space for preaching. Regarding the fragmentation of religious authority, this article is based on the thesis of Eickelman and Anderson, which states that the current religious authorities are those who have succeeded in transmitting religious texts and preaching them through new media. In more detail, this study discusses two important issues, namely the trend of Islamic da'wa on social media and, in particular, the implications of the Islamic views of UHA and Siauw for the emergence of the trend of hijrah Muslim youth. This article concludes that according to UHA, hijrah is a message of Islamic da'wa that not only tells about individual repentance but also as a current trend that young Muslims must follow. Meanwhile, Siauw interprets it as an effort to awaken the spirit of Muslims to achieve the establishment of the Islamic Khilafah.